Admitting evidence of a defendant's previous conviction (PCE) and its impact on juror deliberation in relation to both juror-processing style and juror concerns over the fairness of introducing PCE - Honess, T. M. (Legal and criminological psychology, 2012)
Purpose. To examine the impact of admitting previous conviction evidence (PCE) on juror and jury deliberation. Major questions are: (1) Is there is an association between the inclusion of PCE and confidence in a defendant's guilt using a relatively rich trial simulation? (2) Does PCE invoke jurors’ considerations of fairness to the defendant? (3) Is heuristic processing (HP) associated with a prejudicial interpretation of evidence? Methods. In experiment 1 (n= 82), individual jurors were asked to recall evidence, express opinion, and justify verdicts on the two counts of Affray and Grievous Bodily Harm (GBH). In experiment 2 (new n= 121), PCE information was emphasized and a jury deliberation condition was included. Results. There was no simple association between admitting PCE and judgements of guilt. However, both interviews and jury deliberations indicated careful consideration of evidence. In particular, juror arguments showed that some were troubled by PCE, which they saw as unwarranted and therefore unfair to the defendant. Finally, HP was associated with both a prejudicial focus on the defendant's character and a higher confidence in guilt. Conclusions. A simple link between PCE and judgements of guilt may only hold in relatively circumscribed experimental simulations. Results also indicate that the introduction of PCE is unlikely to aid evidence-based deliberation without careful testing of different forms of judges’ explanation concerning PCE.